EFEKTIVITAS RENDAMAN DAUN RAMBUTAN DALAM PENGENDALIAN VEKTOR MALARIA SETELAH GEMPA - Erlin Yustin Tatontos; I Wayan Getas; Maruni Wiwin Diarti; Urip (Postgraduate, University of Mataram, 2024)
After the earthquake that occurred on the island of Lombok during August 2018 malaria appeared again. The purpose of this study was to determine malaria infection and control of Anopheles sp with Rambutan leaves. The research method uses analytical observation for malaria infection and an experimental with completely randomized design for Anopheles sp. control using natural ingredients, namely rambutan leaves . The population and sample were suspected malaria and Anopheles sp larvae in the working area of ​​the Penimbung Public Health Center in West Lombok District affected by the earthquake. Results of malaria examination studies with RDT/malaria sticks 13% positive for malaria, whereas microscopically 25% positive for malaria. Laboratory test results with rambutan leaf soaking concentrations of 1%, 3%, 6%, 9% and 12% were obtained the higher the concentration the more effective the killing power against larvae of Anopheles sp, with LC50 12.353% and LC90 19.666%. Field test results no larvae in the cupak with the soaking of rambutan leaves. Conclusion, 25% of the population affected by the earthquake were infected with malaria, the most common being plasmodium falciparum, soaking rambutan leaves is effective for controlling Malaria vectors in laboratorium and fields.